Measuring Regional Competitiveness Through The Regional Development Index - Amir, Rismayanti (Universitas Gorontalo, 2024)
This research aims to conduct an analysis focusing on measuring the level of regional competitiveness by utilizing the regional development index as a measure of regional development performance in Luwu Raya. This measurement examines several indicators considered influential, namely economic, social, infrastructure, and environmental aspects. The sample in this research includes all regions in Luwu Raya, comprising Palopo City, Luwu Regency, North Luwu Regency, and East Luwu Regency. The method employed in this research is quantitative analysis using the composite performance index as the analytical technique. The primary steps in constructing a composite index involve weighting, literature studies, trend determination, alternative index determination, and composite index determination. The results reveal that the regional competitiveness in Luwu Raya is unevenly distributed. Palopo City is the region with the highest level of competitiveness, while two regencies, North Luwu and Luwu, have the lowest levels of competitiveness. The most influential aspect of regional competitiveness is infrastructure, as measured by data on the condition of paved roads and clean water distribution. The problem that needs to be addressed in almost all regions of Luwu Raya is poverty. Infrastructure is a pioneering indicator that can have a significant positive or negative impact on development in Luwu Raya. Therefore, it is expected that the government can focus its development policies on infrastructure to provide multiplier effects on economic and social aspects through inclusive economic growth and job creation.